Generation of polyclonal antibodies against Theiler's Murine Encephalomyelitis virus protein 2C, and their use in investigating localisation of the protein in infected cells - Jauka, Tembisa Innocencia (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2010)
The Picornavirus family of positive sense RNA viruses includes some significant human and animal pathogens including Poliovirus (PV), Foot-and-Mouth disease virus (FMDV) and Human Rhinovirus (HRV). The genome is translated within the host cell into a polyprotein that is proteolytically cleaved into the structural and nonstructural proteins. The highly conserved, non-structural protein 2C has numerous roles during the virus life cycle and is essential for virus replication. Although the protein has been well studied in the case of PV, its interactions with the host cell during picornavirus infection is poorly understood. Theiler's Encephalomyelitis virus (TMEV) is a picornavirus that infects mice, and is being used in our laboratory as a model in which to study the 2C protein. In this study, polyclonal antibodies against the TMEV 2C protein were generated and used to localise the protein in infected cells by indirect immunofluorescence. To produce antigen for immunisation purposes, the TMEV-2C protein sequence was analysed to identify hydrophilic and antigenic regions. An internal region of the 2C representing amino acid residues 31-210 was selected, expressed in bacteria and purified by nickel NTA affinity chromatography. Time course analysis of 2C (31-210) showed that the peptide was maximally expressed at 5 hours post induction. The peptide was solubilised using a mild detergent and 1.5 mg of purified antigen was used for immunisation of rabbits. Western blot analysis confirmed that the antibodies could detect both bacteriallyexpressed antigen, and virally-expressed 2C. Examination of virus-infected baby hamster kidney cells by immunofluorescence and confocal microscopy using the antiserum (anti-TMEV 2C antibodies) showed that the protein had a diffuse distribution upon early infection and at later stages it was located in a large perinuclear structure representing the viral replication complex. Furthermore, 2C localised to the Golgi apparatus as revealed by dual-label immunofluorescence using anti-TMEV 2C antibodies and wheat germ agglutinin (WGA). Furthermore, it was shown that TMEV infection results in changes in cell morphology and a redistribution of the cytoskeletal protein, Î²-actin. The successful production of antibodies that recognise TMEV 2C opens the way for further studies to investigate interactions between 2C and hostencoded factors.
Keywords: Picornaviruses; RNA viruses; Immunoglobulins; Encephalomyelitis